Clinical Course of a Covid-19 Patient with Gastrointestinal Symptoms- A Case Report - Sidra Agarwal; Hemanshi Mistry (International Journal of Medical Students, 2020)
Background: COVID-19 most commonly presents with respiratory symptoms. However, it can involve the gastrointestinal tract causing symptoms like diarrhea and the resultant shedding of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in feces. This is due to the virus adhering to angiotensin-converting enzyme 2 receptors largely present in the gastrointestinal tract. This case report recommends routine stool Real-Time Reverse Polymerase Chain Reaction (rRT-PCR) testing for patients presenting with gastrointestinal symptoms. The Case: A healthy 36-year-old male healthcare worker in New York who tested positive for SARS-CoV-2 infection through rRT-PCR of the nasopharyngeal swab. After 7 days of convalescence, he recovered from influenza like symptoms after which he predominantly developed diarrhea, nausea, vomiting and extreme fatigue. Cough was the only lower respiratory symptom during the 3rd week of the clinical course. Anosmia or ageusia preceding the onset of respiratory symptoms was also reported. Due to the outbreak of the pandemic and New York being the epicenter at the time, the patient was recommended to self-isolate with supportive management through antipyretics and electrolyte replacement. Conclusion: This case highlights a SARS-CoV-2 PCR positive patient with predominant gastrointestinal symptoms. The reports regarding virus shedding in feces suggest that SARS-CoV-2 could be transmitted via fecal-oral route and thus routine stool rRT-PCR testing can aid in transmission-based precautions. Furthermore, reports of viral ribonucleic acid present in the stool, suggests direct infectivity of the virus on the intestinal tract. Therefore, screening in patients with only gastrointestinal symptoms can potentially help to contain the virus spread.